Optimal Scheduling Strategy for Wind-Solar-Hydro Alliance Considering Compensation of Regulation by Hydropower - Xianshan LI; Shengbiao DING; Fei LI; Xin LI (Zhongguo dianli)
Aiming at the key problems in cross-region consumption scheduling of the wind-solar-hydro integrated energy, such as the cascade energy storage, cascade hydropower joint regulation and scheduling methods, and fair allocation of hydropower regulation costs, a four-stage optimization scheduling model of wind-solar-hydro alliance is proposed with consideration of the compensation of hydropower flexible regulation costs. Firstly, a wind-solar power fluctuation suppression model based on cascade energy storage regulation is established to minimize the suppression error and cost. A fair allocation method for regulating cost and power of cascade energy storage based on wind-solar fluctuation coefficient is proposed. Secondly, based on the tracking of the power grid load by the joint output of the wind-solar-hydro alliance of the cascade energy storage and cascade hydropower joint regulation, a master-slave game model of wind-solar-hydro alliance and regional power grid is constructed to optimize the power grid price and alliance power sales plan, thus achieving the maximum benefit of both parties. Thirdly, a robust optimization model of the first two-stage scheduling model is constructed with consideration of the uncertainty of wind-solar-hydro, and a energy scheduling strategy is obtained for each entity of the alliance considering both economy and robustness. Finally, an asymmetric Nash negotiation model based on the partner's marginal contribution index is constructed to realize the fair distribution of cooperation surplus and the fair allocation of hydropower regulation costs. The case study results show that the proposed method can fairly improve the net profit of all stakeholders after cooperation, and is conducive to maintaining the stability of alliance cooperation and promoting the cross-regional consumption of wind-solar-hydro integrated energy.